Sífilis Congênita: situação epidemiológica no estado do Rio de Janeiro - Carvalho, I. P.; Guedes, J. C.; Duque, R. R.; Garcia, R. M.; Pinto, P. M.; Costa, L. R. (Congresso Médico Acadêmico UniFOA, 2023)
-